Philosophy of care delivery for spina bifida. Issue 2 (April 2020) - Thibadeau, Judy; Walker, William O.; Castillo, Jonathan; Dicianno, Brad E.; Routh, Jonathan C.; Smith, Kathryn A.; Ouyang, Lijing
Abstract: The multidisciplinary model (MCM) is described as one that utilizes skills and experience from practitioners belonging to various disciplines, each treating patients from a specific clinical perspective. 1 The Spina Bifida Association (SBA) supports and recommends that clinical care for people with Spina Bifida (SB) be provided in specialty clinics of which the MCM is an example; that care be coordinated; and that there be a plan for transitional care. 2 This paper explores the challenges the MCM faces with a transitioning and aging population in a care system that calls for a positive patient experience, engaged health care professionals, desired outcomes, with consideration of cost.